Foreign bank presence and income inequality in Africa: What role does economic freedom play? - Khadijah Iddrisu (Future Business Journal)
Abstract This study contributes to income equality (IE) literature by examining four important issues. First, the study examines the effects of foreign bank presence (FBP) on IE. Second, the paper identifies the minimum threshold level of FBP which can lead to IE. Third, the effect of economic freedom on IE was investigated. Fourth, the paper determines whether economic freedom interacts with FBP to minimise IE. The findings are based on macro data for 33 African countries from 1995 to 2020. The findings from the two-stage system generalised method of moment indicate that unconditionally, FBP reduces income inequality. Also, results from the threshold effect reveal that whilst FBP reduces income inequality, if it exceeds 52%, it may contribute to it. Additionally, the study reveals that economic freedom dampens IIE. Furthermore, economic freedom conditions FBP to reduce IE. Based on these findings, policymakers are advised to exercise caution in attracting foreign banks and to promote local financial institutions. Policymakers are also advised to implement policies to promote economic freedom.